Odpowiedzi

Najlepsza Odpowiedź!
2010-04-05T16:54:55+02:00
A) f(x) = 2x² - 4x + 3 i A = <½; 2>

f(½) = 2 × (½)² - 4 × ½ + 3
f(½) = 2× ¼ + 1
f(½)= 1½

f(2)= 2×2²-4×2+3
f(2)= 2×4-8+3
f(2)= 3

p= -b/2a
p= 1 ∈ <½; 2>

fmin=1
fmax=3.


b) f(x) = -x² + 3x - 1 i A = <-1, 1>

f(-1)= -(-1)² + 3×(-1) -1
f(-1)= -1-3-1
f(-1)=-5

f(1)= - (1)² +3×1-1
f(1)=-1+3-1
f(1)=1

p=1½ ∉<-1, 1>

fmin=1
fmax=-5

c) f(x) = x² + 2 i A = <-2; 3>
f(-2)= (-2)² +2
f(-2)= 4+2
f(-2)=6

f(3)=3²+2
f(3)=9+2
f(3)=11

p=0 ∈<-2; 3>
fimn=0
fmax=11

pozdrawiam ;)
7 3 7